Exploring punk subculture in China - Jian Xiao (2015)
This thesis explores the punk phenomenon in China. In order to examine punk members and practices, an ethnographic research was conducted in large-scale cities, such as Beijing and Shanghai, and small-scale cities, such as Wuhan and Huaihua in China, as well as on the Internet. In particular, the thesis focuses on two prominent themes subculture and resistance as the main directions of analysis. Through discussing findings from the three dimensions of the individual, collective and online, it is argued that the Chinese punk phenomenon exists as a subculture and punk subcultural practices can be regarded as manifesting forms of resistance in China. First, this study presents a detailed individual biography of one punk musician and then further examines those of other participants. It is discovered that subcultural resistance can have a different impact at different stages of a person s life. Second, this study demonstrates forms of collective practices and how they are manifested, and reveals how Chinese punk subculture members collectively produce different forms of subcultural resistance. Finally, this study examines Chinese punk online. It focuses on how online group members produce meanings of their activities and deploy specific techniques to resist online norms and censorship. Overall this thesis contributes to the ongoing discussions in current field of subcultural studies. By providing a study on punk subculture in China, the research engages empirically in the question of power relations in a society from both individual and collective levels, which has rarely been undertaken before.